Evaluation on Container Products in East Nilam Terminal, Tanjung Perak Port - Haris Zonakis Timor (Journal of the Civil Engineering Forum, 2016)
Development of a container terminal is needed due to a change in the region, cargo handling, ship technology, and changes in quantity demand. Performance indicators of container terminal container is needed to assess the streamlined of container terminals' operational process in serving the transportation of goods and development activities in the future. The analysis of performance indicator in container terminal will have an impact on improving the current services and future. Therefore, there should be a study to measure the performance indicator in ports or container terminals, especially in the Multipurpose Terminal East Nilam (TMNT) as an object of research. Performance of container terminal as a system with many variables influence can be analyzed with the forecasting method and related theory of applicable equations as well as the application of the model scenarios. Forecasting methods are used to determineTMNT for short-term conditions (2020), medium term (2030), and long-term (2040). The results of the data analysis for the research activities of the secondary data obtained from PT. IPC III branch of Tanjung Perak in 2013, obtained the performance TMNT including BOR (performance dock) 51% and YOR (yard performance)31%. The analysis shows that in 2040, needs a dock length of about TMNT 1,254 meters by nine moorings from existing conditions along the 320 meters with two moorings. The length of East Nilam pier that is not in the revitalization is 540 meters. The development of infrastructure is only possible along the pier 860 meters with six moorings. While the CY area needs about 5 acres from existing condition, which is around 3.8 acres. BOR value and YOR projection reach up to 161% and 145%. This evidence means that the TMNT with existing conditions cannot be used again in 2040. The application of C scenario model by adding 860 meters of dock length with six moorings, will add capacity of the dock up to600,000 TEUs, and elimination of not operating time is capable to lowering the value of the BOR become 41% and YOR become 69%.